Aplikasi Pemesanan Buket Berbasis Web Pada Toko Anastha_Craft - Pusvita, Ester Ayuk; S, Natalia . Setyaningrum (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
The bouquet ordering system at Anastha_Craft, a small business located in Nabire, faces several main issues. These include limited customer reach due to the store's physical location being far from the city, restricted operating hours, and a manual ordering system that does not provide complete and real-time product information. To address these problems, the research uses the Rapid Application Development (RAD) method to develop a website-based ordering application. RAD was chosen for its flexibility in adapting to changing requirements during the development process. This ordering system is built using PHP programming language and a MySQL database, with three main stages: Requirements Planning, Design Workshop, and Implementation. The developed application allows customers to place orders online, extends the store's service reach, and facilitates product data management. The results of the study show that the implementation of this website-based system successfully improved operational efficiency, made product information more accessible to customers in real-time, and supported the business growth of Anastha_Craft